2020
DOI: 10.1063/1.5131631
|View full text |Cite
|
Sign up to set email alerts
|

Invasive electrical impedance myography at different levels of contraction of gastrocnemius muscle of rat

Abstract: Electrical impedance myography (EIM) is as an experimental technique that associates muscle impedance with muscular activity. Changes in muscle impedance during contraction occur mainly due to changes in the morphological and physiological characteristics of muscles that lead to different impeditivities in comparison with the resting condition. There is no consensus on the details of muscular impedance during muscle activity. EIM measurements on humans are also influenced by factors such as the electrode–skin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…Our findings indicated that this combination could also reveal the changes in properties of target muscle directly during force generation ( Li et al, 2016c ). Likewise, the relationship between the EIM data and force production was verified in animal experiments ( Li et al, 2016a ; Coutinho et al, 2020 ). These insights might be beneficial when further extended to clinical assessments of alterations in force production after stroke.…”
Section: Combination Of Eim and Contractile Property Assessmentmentioning
confidence: 73%
See 1 more Smart Citation
“…Our findings indicated that this combination could also reveal the changes in properties of target muscle directly during force generation ( Li et al, 2016c ). Likewise, the relationship between the EIM data and force production was verified in animal experiments ( Li et al, 2016a ; Coutinho et al, 2020 ). These insights might be beneficial when further extended to clinical assessments of alterations in force production after stroke.…”
Section: Combination Of Eim and Contractile Property Assessmentmentioning
confidence: 73%
“…Strength test Rutkove et al, 2014a;Shellikeri et al, 2015;Zaidman et al, 2015 • The observed relationship between EIM and strength tests suggested that EIM had the potential as a meaningful measure in the diagnosis of neuromuscular diseases. Li et al, 2016a,c;Coutinho et al, 2020 • The combination of EIM and strength test has the potential to directly reveal the changes in the force generation properties of the target muscle.…”
Section: Contractile Property Assessmentmentioning
confidence: 99%
“…On the other hand, changes in the X value are related to changes in the features of the cell membrane and layers of tissue ( 36 ). Coutinho et al ( 37 ) suggested that changes in X were likely to be caused by changes in the features of the cellular membranes. In this study, the R and Z values increased significantly at 5 kHz in the CLBP group.…”
Section: Discussionmentioning
confidence: 99%
“…Changes in X value are related to changes in features of the cell membrane and layers of tissue [28]. Coutinho et al [29] suggested changes in reactance were likely brought about by changes in the features of the cellular membranes.…”
Section: Discussionmentioning
confidence: 99%